The assembly and performance of button primary alkaline Zn-MnO2 battery - Muhammad Faheem Ho (Nanyang Technological University, 2020)
The need for new energy storage technology is highly sought after as advancement in technology pushes manufacturers to meet a growing demand for new and innovative inventions to create, improve and optimise new and current technologies. This report will focus on the assembly and characterisation of primary alkaline Zn- MnO2. The report consists of three parts. The present data and results were obtained through analysing the performance of the battery system from the numerous experiments using several fabrication techniques and ratios of reactants. The first phase of the research was to familiarise with the fabrication procedures of making a miniature button battery from scratch. This consists of the packing of cathodic and anodic material, sealing techniques and the discharging testing. The second phase was to study the effects of the assembly parameters of the system and the ingredients on the performance of the battery, mainly the discharging curve of the system. The final phase commences with optimising the reactant ratio and fabrication such as using a compacting device to form pallets and a hydraulic crimpling machine for sealing. These techniques were implemented after several rigorous testing of different techniques as to improve and obtain the best results. The improvements were attributed to the increase of the contact area and successful reduction of the side reaction that would lead to the gassing phenomenon in batteries. Ultimately, the research have made some discoveries about the effects of the assembly on the performance on the system such as workability and shelf life. Overall, the study is very informative and there is room for improvement, however, with continuous advancement in the primary battery field, it could lead to a variety of engineering application.